Acúmulo de matéria seca e nutrientes de híbridos de sorgo sacarino em condições de safrinha em Selvíria-MS - Pivetta, Raul Sobrinho [UNESP] (2014)
The study of nutrient uptake rate has great importance to increase of efficiency in the crop management however, to energetic plants as sweet sorghum, the characterization of technological quality of juice also is necessary for good crop performance. This work had as objective to determine curves of dry matter accumulation and nutrients and verify the technological quality of sweet sorghum hybrids. It were used the hybrids Advanta 81981 and CV 147 in an experimental design in randomized blocks, with the treatments arranged in split-splot in time, main treatments were the two sweet sorghum hybrids and the secondary, the samples. The samples were collected in each 15 days after emergence and separated in leaves, stalk and panicles. It was determinated the dry mater of each part of plant and the content of macro and micronutrients to quantify the accumulation in the shoot and, at last seasons of sample was seek the technological quality of biomass. The hybrids Advanta 81981 and CV 147 accumulated dry matter along the cycle and produced 17,400 and 16,170 kg ha-1 of dry matter, respectively. It were observed the greatest nutrients accumulation at flowering period, in both sweet sorghum hybrids. Nutrients accumulation on the shoots follow this order: K > N > Mg > Ca > P > S > Fe > Mn > Zn > Cu. The modern sweet sorghum hybrids accumulate the double of P and K, in the shoots, in comparison to old varieties. The hybrids Advanta 81981 and CV 147 show good values of industrial quality of biomass to harvest between 105 and 120 DAE, when cultivated in second season, at Selvíria-MS season